Multifaceted core-shell nanoparticles: superparamagnetism and biocompatibility - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Ahir, Manisha; Adhikary, Arghya; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2015)
NicoreAgshell nanoparticles were synthesized by redox transmetallation reaction. Reduction potential match was encouraging to attempt the synthesis of the NicoreAushell system too. However, it could be achieved only after an effective surface modification on the Ni-core. Thorough characterization (UV-Vis spectroscopy, fluorescence spectroscopy, XRD, XPS, FTIR, TEM, and EDX) proved the necessity of surface modification and the success of synthesis of both types of core-shell structures. The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirmed the surface modification of Ni nanoparticles and the interactions involved between the ligands and metals (in the core and/or the shell) at various steps of the synthetic process. Even after the formation of the noble metal shell, the magnetic core was found to retain its superparamagnetic nature. In addition, the Au-shell protected the core from aerial oxidation and decreased toxicity as compared to pristine Ni nanoparticles as observed by MTT assay on normal cells (PBMCs).